Synthesis of the Arts with the Region - Mejrema Zatrić (Docomomo Journal)
Some of Juraj Neidhardt’s most emblematic projects are situated in pristine, non-urban settings. From the Ski House in the pine forests of the Bosnian hills to the Hotel Agava immersed in the Mediterranean shrubbery of the Adriatic Coast, his designs in the landscape were key for him to define his architecture as seeking proximity to and harmony with nature. The design strategy that Neidhardt utilized to realize this ambition was, however, far from constant. While in the 1950s, he relied solely on the “unwritten laws” of the vernacular models to define techniques of new design integration into the specific regional environment, in the 1960s, he produced a series of striking artistic compositions of natural and architectural visual elements, which he described with the notion of “phantasy in tourism.” This paper analyzes Neidhardt’s writings and several projects of the 1950s and 1960s in order to situate his 1960s architecture excursus into the visual arts within the post-war discourse of the “synthesis of the arts.” Under the influence of his and Dušan Grabrijan’s geography-informed understanding of the unity between art, life, and the regional environment and his research in the regional planning of tourism (both presented in the book Architecture of Bosnia and the Way towards Modernity (Grabrijan & Neidhardt, 1957), Neidhardt developed an original architectural language that synthesized not only architecture and sculpture but also the specific regional landscape into one harmonious visual whole. This aesthetic synthesis, however, communicated a deeper synthesis between architecture, geographic region, and modern state economy, facilitated by the emerging regional planning as the ultimate absorption of the total environment into the comprehensive kind of modernism.